Teknik Relaksasi Genggam Jari Pada Pasien Ileus Obstruksi Untuk Menurunkan Intensitas Nyeri Post Laparoskopi - Netti, Netti; Maylanda, Yohana (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2023)
Pain in laparoscopic procedures is brief but of high intensity. Overcoming pain requires management of pain management through pharmacological and non-pharmacological ways. relaxation technique that can reduce pain after surgery is the finger grip relaxation technique.This study aims to apply finger-held relaxation techniques to reduce the intensity of post-laparoscopic pain. The design of this research is a type of descriptive observational research in the form of a case report . Research time from 15 May to 3 June 2023 . The population of all obstructive ileus patients who were performed laparoscopically in the men's operating room at Dr.M Djamil Hospital, Padang. The sample is 2 people The results of the application showed that there was a decrease in pain intensity, namely before the finger-held relaxation technique was carried out, namely 7-6 and after the finger-hand-held relaxation technique was carried out, namely 5-3. The suggestion for this research is that the finger-held relaxation technique can be used as an intervention that nurses can do to reduce the intensity of post-laparoscopic pain.